Passionate Histories Myth, memory and Indigenous Australia - Peters-Little, Frances (Aboriginal History Monograph, 2010)
This book examines the emotional engagements of both Indigenous and Non-Indigenous people with Indigenous history. The contributors are a mix of Indigenous and Non-Indigenous scholars, who in different ways examine how the past lives on in the present, as myth, memory, and history. Each chapter throws fresh light on an aspect of history-making by or about Indigenous people, such as the extent of massacres on the frontier, the myth of Aboriginal male idleness, the controversy over Flynn of the Inland, the meaning of the Referendum of 1967, and the policy and practice of Indigenous child removal.